Investigation of near-infrared laser diodes for application in space-based spectroscopic gas sensing - McInerney, David (Trinity College (Dublin, Ireland). School of Physics, 2007)
The availability of numerous semiconductor diode lasers that provide wavelength tuneable, high output power, single frequency emission in the near infrared region of the spectrum (0.7μm - 2.5μm) provides researchers with a reliable and compact source of monochromatic radiation. Originally, development of this technology was driven by the telecom m unications industry, however the fact that the overtone/combination absorption spectra of several gas species match the emission frequency of these laser sources have presented countless benefits for spectroscopic sensing applications.
Keywords: Physics, Ph.D.; Ph.D. Trinity College Dublin